Analysis of Incidence in Elderly and Old Age Persons Affecting Active Labor Activitie - Shavkat Mamirovich Turdiev (Zien Journals, 2022)
The elderly are a rapidly growing socio-demographic group, making up one fifth of the country's population, and by 2025 the number of people over 60 will exceed one billion, which will be 16% of the total population of our planet. In this regard, there is a problem of maintaining the quality of life of the elderly. The health status and morbidity patterns of older people are significantly different from those in other age groups. In this regard, the problem of the health of the elderly and senile is becoming relevant both for the Republic of Uzbekistan and for many countries of the world. Among the factors that determine public health, lifestyle factors and the availability of medical and social assistance play an important role.
Keywords: elderly people; elderly patients; old age; morbidity